Crystal structure of a peptidyl‐dipeptidase K‐26‐DCP from Actinomycete in complex with its natural inhibitor. (6th November 2016) - Masuyer, Geoffrey; Cozier, Gyles E.; Kramer, Glenna J.; Bachmann, Brian O.; Acharya, K. Ravi
Abstract : Several soil‐derived Actinobacteria produce secondary metabolites that are proven specific and potent inhibitors of the human angiotensin‐I‐converting enzyme (ACE), a key target for the modulation of hypertension through its role in the renin–angiotensin–aldosterone system. K‐26‐DCP is a zinc dipeptidyl carboxypeptidase (DCP) produced by Astrosporangium hypotensionis, and an ancestral homologue of ACE. Here we report the high‐resolution crystal structures of K‐26‐DCP and of its complex with the natural microbial tripeptide product K‐26. The experimental results provide the structural basis for better understanding the specificity of K‐26 for human ACE over bacterial DCPs. Database: Structural data are available in the PDB under the accession numbers5L43 and5L44 . Abstract : Astrosporangium hypotensionis produces complex peptide secondary metabolites. One such peptide, K‐26, is a weak inhibitor of the organism's own zinc peptidase K‐26‐DCP, but is a strong inhibitor of human ACE. Analysis of the structure of K‐26 peptide in complex with K‐26‐DCP presented here, compared with those of K‐26 in complex with ACE homologues, provides a structural basis of K‐26 recognition.